2014
DOI: 10.14419/ijbas.v3i3.2473
|View full text |Cite
|
Sign up to set email alerts
|

Bud, leaf and stem essential oil composition of Syzygium aromaticum from Madagascar, Indonesia and Zanzibar

Abstract: Syzygium aromaticum essential oil is widely used in dental care, as an antiseptic and analgesic and is effective against a large number of bacteria. The major component of clove essential oils is usually considered to be eugenol, with β-caryophyllene and eugenyl acetate, being present although in lower concentrations. A review of published results reveals a great variability in the chemical composition of clove essential oils. The purpose of this study is to compare the chemical composition of Madagascar, Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 21 publications
1
18
1
1
Order By: Relevance
“…The antioxidant, anti-inflammatory [ 48 ], antimicrobial [ 49 ], and analgesic [ 50 ] effects of eugenol have been previously documented. The oil is also composed of numerous other compounds, including eugenol acetate, β-caryophyllene, and α-humulene [ 51 ]. Generally, data on the cytotoxicity of EOs and their active cytotoxic components are limited.…”
Section: Clove Essential Oilmentioning
confidence: 99%
“…The antioxidant, anti-inflammatory [ 48 ], antimicrobial [ 49 ], and analgesic [ 50 ] effects of eugenol have been previously documented. The oil is also composed of numerous other compounds, including eugenol acetate, β-caryophyllene, and α-humulene [ 51 ]. Generally, data on the cytotoxicity of EOs and their active cytotoxic components are limited.…”
Section: Clove Essential Oilmentioning
confidence: 99%
“…Several studies indicate that eugenol, β-caryophyllene and eugenyl acetate are the major compounds of the essential oil of S. aromaticum with varying percentages [24,26,[28][29][30][31][32][33][34][35].…”
Section: Yield and Chemical Compositionmentioning
confidence: 99%
“…Previous investigations have demonstrated that the chemical composition of S. aromaticum essential oil can be influenced by the condition of the environment, the genotype, the geographical origin, the period of harvest, the place of drying, the temperature and the duration of drying and the method of extraction [4,32,27].…”
Section: Yield and Chemical Compositionmentioning
confidence: 99%
“…Jirovetz et al [14] reported that clove leaf essential oil comprises more than 20 chemical compounds with eugenol (76.8%), followed by β -caryophyllene (17.4%), α -humulene (2.1%), and eugenyl acetate (1.2%) as the main components. On the other hand, clove bud essential oil mainly comprises eugenol (72%) but higher concentration of eugenyl acetate (8%) yet lesser β -caryophyllene (2.8%) than the bud-derived essential oil [15]. Clove leaf extract has been reported to have a radical scavenging activity based on the DPPH assay [14].…”
Section: Introductionmentioning
confidence: 99%